Learning identities, education and community young lives in the cosmopolitan city - Erstad, Ola (Cambridge University Press, 2016)
This book offers a case study of children and young people in Groruddalen, Norway, as they live, study and work within the contexts of their families, educational institutions and informal activities. Examining learning as a life-wide concept, the study reveals how 'learning identities' are forged through complex interplays between young people and their communities, and how these identities translate and transfer across different locations and learning contexts. The authors also explore how diverse immigrant populations integrate and conceptualize their education as a key route to personal meaning and future productivity. In highlighting the relationships between education, literacy and identity within a sociocultural context, this book is at the cutting edge of discussions about what matters as children learn
Title from publisher's bibliographic system (viewed on 04 Jul 2016)
Keywords: Erziehung; Gesellschaft; Education / Social aspects / Norway / Groruddalen / Case studies; Learning / Social aspects / Norway / Groruddalen / Case studies; Community and school / Norway / Groruddalen / Case studies; Multicultural education / Norway / Groruddalen / Case studies; Norwegen; Fallstudiensammlung